La creación de la Sala del Pueblo Sami en el Museo Nacional de las Culturas del Mundo de la Ciudad de México - Mosquera Delgado, Luis Alejandro (2024)
The following is a brief review of the creation process of the Sala del Pueblo Sami (Sami People’s Hall) in the Museo Nacional de las Culturas (MNCM, National Museum of World Cultures, Mexico City), of the Instituto Nacional de Antropología e Historia (INAH, National Institute of Anthropology and History). The purpose of this work is to reflect on this type of experience as an essential part of the training of postgraduate students in Museum Studies and Practices of the Escuela Nacional de Restauración, Museografía e Historia (ENCRyM, National School of Conservation, Restoration and Museography), also part of the INAH. A continuación se presenta una breve reseña del proceso de creación de la Sala del Pueblo Sami en el Museo Nacional de las Culturas del Mundo (MNCM, Ciudad de México), del Instituto Nacional de Antropología e Historia (INAH). La finalidad es reflexionar sobre este tipo de experiencias como parte esencial en la formación de estudiantes del posgrado en Estudios y Prácticas Museales de la Escuela Nacional de Conservación, Restauración y Museografía (ENCRyM), también del INAH.